Early Control of Highly Pathogenic Simian Immunodeficiency Virus/Human Immunodeficiency Virus Chimeric Virus Infections in Rhesus Monkeys Usually Results in Long-Lasting Asymptomatic Clinical Outcomes - Igarashi, Tatsuhiko (American Society for Microbiology, 2003)
In contrast to simian immunodeficiency viruses (SIVs), which induce immunodeficiency over a 1- to 2-year period, highly pathogenic simian-human immunodeficiency viruses (SHIVs) cause an irreversible and systemic depletion of CD4(+) T lymphocytes in macaque monkeys within weeks of inoculation. Nonetheless, the seemingly more aggressive SHIVs have proven to be easier to control by the same vaccine regimens which fail to contain SIV. Because early events during in vivo infections may determine both the pathogenic consequences of the challenge virus and its sensitivity to interventions that prevent disease, we have evaluated the effects of inoculum size and a potent antiretroviral drug on the development of disease in monkeys infected with SHIV(DH12R). The results obtained show that in a majority of inoculated animals, suppression of SHIV replication during the first 2 weeks of infection, which prevents complete loss of CD4(+) T cells, leads to very low to undetectable postpeak viremia and an asymptomatic clinical course for periods up to 4 years.